2017
DOI: 10.5455/jice.20170522103525
|View full text |Cite
|
Sign up to set email alerts
|

Use of traditional plants in management of Halitosis in a Moroccan poulation

Abstract: Introduction:The use of medicinal plants was a very spread therapeutic way. At present, several studies are moving toward this ancestral option, seen the emergence of several bacterial resistance and for the large number of side effects of some synthetic drugs.Objective:The objective of this study was to collect and evaluate information on medicinal plants commonly used in five Moroccan cities: Rabat, Salé, Témara, Khémisset, and Tiflet for the management of halitosis.Methods:This is a cross-sectional survey; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 46 publications
0
10
0
1
Order By: Relevance
“…However, there are few reports on the effects of Moroccan EOs on periodontal pathogens. The EO of O. vulgare was selected for this study on the basis of its traditional use for the treatment of oral diseases [13].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, there are few reports on the effects of Moroccan EOs on periodontal pathogens. The EO of O. vulgare was selected for this study on the basis of its traditional use for the treatment of oral diseases [13].…”
Section: Discussionmentioning
confidence: 99%
“…Morocco has, by its geographical diversity, great natural resources for cultivation of medicinal and aromatic plants. Surveys performed in Morocco among the population in different regions have shown a frequent therapeutic use of this natural heritage in traditional medicine [12,13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plants and other natural products have been extensively used in the management of oral infections and improvement of oral health in many populations (Akkaoui & Ennibi, ; Chinsembu, ). Among several tested herbal plants, we found that extract of leaves or twigs from Psidium guajava efficiently neutralizes the activity of A. actinomycetemcomitans leukotoxin (Kwamin, Gref, Haubek, & Johansson, ).…”
Section: Introductionmentioning
confidence: 99%
“…Several recent studies related to the use of S. aromaticum extract and its essential oil content for the treatment of periodontal diseases including halitosis have been reported. A cross-sectional survey by Akkaoui and Ennibi (2017) reported that there were 23 medicinal plants including clove commonly used by Moroccan herbalists for the treatment of halitosis. A study by Kaur and Chandrul (2017) showed that the main component of clove oil was eugenol, with β-caryophyllene and eugenyl acetate; but the contents of essential oils in cloves were found to be various depending on their anatomic and geographical origins.…”
Section: Introductionmentioning
confidence: 99%